Strategies for Promoting Innovation in a Driving Training Programme that Implements the Independent Curriculum - Elizabeth Patras, Yuyun; Abdul Gani, Resyi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This research aims to find new ways and strategies to increase innovation in the teacher school program by examining other variables positively related to teacher innovation. These variables implement an independent curriculum. New ways and strategies for enhancing teacher innovation are subsequently recommended to the following parties. The parties are the Director of Education, School Supervisors, School Principals, and Teachers. 183 respondents were involved as a multi-stage random sample using the Slovin formula. It also used quantitative research with correlation analysis modelling and SITOREM analysis. The research results indicate that (1) there was a positive direct relationship between the innovation strategy and the driving school programme with a value of ry1 = 0.991, (2) there was a positive direct relationship between the driving school programme and the implementation of the independent curriculum with a value of ry2 = 0.982, (3) there was a positive direct relationship between the implementation of the independent curriculum and the teacher's innovative strategy with a value of ry3 = 0.986, (4) there was a positive direct relationship between the implementation of the independent curriculum and the teacher's innovative strategy with a value of ry3 = 0.986.986 (4) there was a positive direct relationship between the driving school curriculum and implementing the independent curriculum with teacher innovation strategy with a value of ry12 = 0.992, (5) there was a positive direct relationship between the driving school program and implementing the independent curriculum with a value of ry13 = 0.992, (6) there is a positive direct relationship between the driving school programme and the implementation of the independent curriculum with an innovation strategy with a value of ry23 = 0.989, and (7) there is a positive direct relationship between the driving school programme and the implementation of the independent curriculum with an innovation strategy with a value of ry123 = 0.992. The research explores strategies to increase teacher innovation through the development of achievement motivation, teamwork, and organisational climate. The SITOREM analysis results reveal that the indicators are still weak and need to be improved, namely 1) management innovation, 2) service innovation, and 3) process innovation.